Alternative Social Safety Nets in South Sudan : Costing and Impact on Welfare Indicators -- Poverty Note - Pape, Utz (World Bank, Washington, DC, 2015)
The purpose of this note is to provide the monetary cost of various social safety net targeting schemes that can be deployed to reduce vulnerability and increase resilience. It is believed that gradually switching to the provision of social safety nets can reduce the chronic dependency on humanitarian (mainly food) aid. At the same time, it could help to alleviate reliance on patronage networks and switch a portion of the public spending from unproductive uses (e.g., military expenditure) toward strengthening the resilience and supporting the livelihoods of South Sudanese. In addition, a social safety net would address the fatigues of years of weak governance and ongoing efforts to find more direct, transparent ways to enable citizens to reap the benefits of independence and – once it materializes – peace.